Identifying the needs and assets of the learner with diabetes in the Foundation Phase - Bender, C.J.G. (Cornelia Johanna Getruida) (University of Pretoria, 2013)
Dissertation (MPhil (Education for Community Development))--University of Pretoria, 2004.